Kirtimukha images on the pillar in the Antarala - Temples of India Project Team (Jio Institute, 2024)
The pillars in the antarala (vestibule or antechamber) are adorned with kirtimukhas (face of glory) motifs that emit festoons. Placed above these kirtimukhas are half medallions which are skillfully carved, depicting geese, kinnaras (composite half-bird, half-woman creatures) and fully bloomed flowers. The representation of the goose is also notable here.